Royal jelly abrogates flouride-induced oxidative damage in rat heart tissue by activating of the nrf-2/NF-?B and bcl-2/bax pathway - Aslan, Abdullah; Beyaz, Seda; Gok, Ozlem; Can, Muhammed Ismail; Parlak, Gozde; Ozercan, Ibrahim Hanifi; Gundogdu, Ramazan (Taylor & Francis Ltd, 2021)
Royal jelly is known to strengthen memory, provide antioxidative, antidiabetic, antitumor, anticancer, antibacterial, antiinflammatory, antihypertensive. In this study, 42 rats (n = 42) were used, and these rats were divided into 6 groups of 7 rats each. Groups: (i) Control Group: Group fed with standard diet; (ii) Royal Jelly (RJ) Group: RJ (100 mg/kg bw, gavage); (iii) F50 Group: Fluoride (50 mg/kg bw, drinking water); (iv) F100 Group: F (100 mg/kg bw, drinking water); (v) F50 + RJ Group: F (50 mg/kg bw, drinking water) + RJ (100 mg/kg bw, gavage); (vi) F100 + RJ Group: F (100 mg/kg bw, drinking water) + RJ (100 mg/kg bw, gavage). The rats were decapitated after 8 weeks, and their heart tissues were taken and examined. Lipid peroxidation by MDA (malondialdehyde) analyzes, GSH (glutathione) level and catalase activity were determined by spectrophotometer. Protein expression levels of caspase-3, caspase-6, caspase-9, Bcl-2, Bax, BDNF, Gsk-3, Nrf-2 and NF-kappa B proteins in heart tissue were determined by western blotting technique and hearth tissue evaluated by histopathologically. As a result, MDA levels, Bcl-2, Gsk-3 and NF-kappa B protein expression levels were reduced, whereas GSH levels, caspase-3, caspase-9, caspase-6, Bax, BDNF and Nrf-2 protein levels were increased in the F50 + RJ and F100 + RJ groups compared to the F50 and F100 groups. According to the results of this study, it has been concluded that Royal jelly has the potential to be developed in to a drug for treatment of heart diseases in addition to providing protection against heart damage.
Keywords: Bax; Gsk-3; Fluoride; Heart tissue damage; Royal jelly